Performance differences and energy balance in matched male and female ironman triathletes - Kimber, N. E.; Ross, J. J.; Mason, S. L.; Speedy, D. B. (Medicine & Science in Sports & Exercise, 1998)
This study evaluated whether females can outperform performance-matched males during an ultra-distance triathlon. Ss (M = 11; F = 9) were tested in a laboratory prior to competing. One male and one female did not complete the event leaving five matched-pairs. Comparison of finishing times showed females to be significantly faster than males. No significant differences in energy or energy intake were found. The greater endurance capacity of females did not appear to be related to energy balance. Implication. Females function more efficiently in endurance events than do performance-matched males.